Robotic transanal minimally invasive surgery for local excision of rectal neoplasms. (13th March 2014) - Hompes, R; Rauh, S M; Ris, F; Tuynman, J B; Mortensen, N J
Abstract: Background: Robotic transanal minimally invasive surgery (TAMIS) may be an option for rectum-preserving excision of neoplasms. Recent cadaveric studies showed improved vision, control and manoeuvrability compared with use of laparoscopic instruments. This study reports the clinical application. Methods: Consecutive patients eligible for transanal endoscopic microsurgery (TEM) or TAMIS in three participating centres were operated on using a robotic platform and transanal glove port. Patient demographics, lesion characteristics, perioperative data, complications and follow-up of all patients were recorded prospectively. Results: Sixteen patients underwent robotic TAMIS for rectal lesions with a median (range) distance from the anal verge of 8 (range 3–10) cm. The median size of the resected specimen was 5·3 (0·5–21) cm 2 . The median docking time and duration of operation were 36 (18–75) and 108 (40–180) min respectively. One conversion to regular (non-robotic) TAMIS was needed owing to difficulties accessing the rectum. Glove puncture necessitated replacement in four procedures, an unstable pneumorectum arose during one operation and one patient developed a pneumoperitoneum. One patient required catheterization for urinary retention. The median hospital stay was 1·3 (0–4) days. The additional cost of the robotic approach was approximately €1000 per procedure (excluding the capital expenditure on the robotic system and its maintenance). Conclusion: Robotic TAMIS is feasible in patients with rectal lesions. Potential advantages over TEM and non-robotic TAMIS will need to be balanced against the cost of the robotic system. Abstract : Promising but costs prohibitive